A companion to Luis Buñuel - Edwards, Gwynne (Colección Támesis. Monografías, 2005)
Luis Bu©łuel [1900-1983] was one of the truly great film-makers of the twentieth century. Shaped by a repressive Jesuit education and a bourgeois family background, he reacted against both, escaped to Paris, and was soon embraced by Andr©♭ Breton's official surrealist group. His early films are his most aggressive and shocking, the slicing of the eyeball in Un Chien andalou [1929] one of the most memorable episodes in the history of cinema. The Forgotten Ones [1950] and He [1952], made in Mexico, were followed, from 1960, in Spain and France, by the films for which he is best known: Viridiana [1961], Belle de jour [1966], Tristana [1970], The Discreet Charm of the Bourgeoisie [1972], and That Obscure Object of Desire [1977]. Gwynne Edwards analyses the films in the context of Bu©łuel's personal obsessions - sex, bourgeois values, and religion - suggesting that the film-maker experienced a degree of sexual inhibition surprising in a surrealist.